THEMATIC PROGRESSION IN THESIS ABSTACTS WRITTEN BY ENGLISH STUDENTS OF FBIB UNISBANK SEMARANG - Liliek Soepriatmadji (Universitas Stikubank (UNISBANK) Semarang, 2009)
This study examines the pattern of thematic progression (TP) in the abstracts written by English students of FBIB Unisbank Semarang. Twenty five abstracts are randomly taken from which the sentences are analyzed to show their thematic patterning. The theory proposed by Danes (1974) was used as the framework to analyze the pattern employed in the abstracts and the result of which indicates that the split rheme TP pattern (77%) is realized in the abstracts and theme-derived TP pattern (23%) is also noticed. The study also describes that the link between linguistic thematic progression and the messages is characterized by the use of speech functions (SF) as declarations (33%), representatives (50%) and directives (17%). It is sufficient to say that students display good experience in writing their abstracts but to further justify that the abstracts are standard ones future researchers may conduct similar studies by employing more data and schematic structure analysis on abstracts. Key words: thematic progression, abstract, speech function